Preparation of flexible zinc oxide/carbon nanofiber webs for mid-temperature desulfurization - Kim, Soojung; Bajaj, Bharat; Byun, Chang Ki; Kwon, Soon-Jin; Joh, Han-Ik; Yi, Kwang Bok; Lee, Sungho (ELSEVIER, 2014)
Polyacrylonitrile (PAN) derived carbon nanofiber (CNF) webs loaded with zinc oxide (ZnO) were synthesized using electrospinning and heat treatment at 600 C. Uniformly dispersed ZnO nanoparticles, clarified by X-ray diffraction and scanning electron microscopy, were observed on the surface of the nanofiber composites containing 13.6-29.5 wt% of ZnO. The further addition of ZnO up to 34.2 wt% caused agglomeration with a size of 50-80 nm. Higher ZnO contents led the concentrated ZnO nanoparticles on the surface of the nanofibers rather than uniform dispersion along the cross-section of the fiber. The flexible composite webs were crushed and tested for hydrogen sulfide (H2S) adsorption at 300 degrees C. Breakthrough experiments with the ZnO/CNF composite containing 25.7 wt% of ZnO for H2S adsorption showed three times higher ZnO utilization efficiency compared to pure ZnO nano powders, attributed to chemisorption of the larger surface area of well dispersed ZnO particles on nanofibers and physical adsorption of CNF. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: CHEMICALLY ACTIVATED CARBONS; HYDROGEN-SULFIDE ADSORPTION; VAPOR ADSORPTION; H2S; OXIDE; REMOVAL; SULFUR; OXIDATION; GRAPHENE